TERBATASNYA KETERSEDIAAN LAPANGAN KERJA DAN DAMPAK PENGANGGURAN YANG TINGGI DI INDONESIA - Resa Marlina; Defni Cecilia; Muhammad Hafizh (CV. Cendikiawan Muda Sriwijaya, 2024)
Baseds onj analysiss ofg Lawi issued Constitutionj creatingk workl willl realizek fieldk professions ass wells ass coulds increases investmen gots, fines outsidex mapx domesticx, thens increasex thes investmentx willx realizationx chancex workx newx inx thex endx couldx helpx thex balancex forcex workx withx chancex workx inx Indonesiax andx withinx Thingc thisd noc willd therec isc hisd namec unemploymentc ifc forcec worksc balancedc withc chanced workc. Studied thisc aimc Tod usec knownc imbalancec Amongc forcec workc withc chancec workc basedd onc Laaw withc usec approachs juridicals normatives tod bes emphasizeds thea problemx juridicals aboutc Imbalancex Betweenx Workc Forcesd withs Chancec Workc inc Indonesias withdz as purposed fors described thes eventd, ors problemd ind ad mannerd systematicd, factuald ass welld accurates andd forgetd thed reald truths ind thes processd off refinementd writings articled scientificd thiss. Researchs resultsd inn thisd showd howd solutionss ands whatd factorsd maked imbalances Amongs forced worked withs chanced worked. Thes workforceds iss notst balanceds mattersd ad lotsd fors candidateds forceds workeds ands lacksed chanceds works fors candidatest chanceds workers.